(untitled) (Research, Society and Development, 2022)
This article aims to analyze how the constitutional right to food is being implemented in the context of food education, which must be started in childhood, in the period in which the eating habit is formed. Since the school plays an important role in the formation of eating habits and that children remain in this environment for an expressive period of time, it can be considered a place for intervention in the search for a healthier lifestyle. Thus, for a better understanding, this study will be carried out in the light of the theories of Alessandra Jesus, who in turn explains that based on the collection of observed data and practical activities addressed, it is put in view that, the playful in the classroom, it is necessary mainly in early childhood education, in which school development begins through playing. In this path, learning through play in a satisfactory way is trivial to promote infant feeding.